The Role Of Doctors And Nurses In Hiv/Aids Handling Efforts Of The Gays - Ludgardis Ramni; A Widanti S; Hadi Sulistiyanto (Universitas Katolik Soegijapranata Semarang, 2018)
Health was one of the important and main elements in improving community’s welfare. Doctors and nurses were part of health workers providing health services to the community to improve their health status, including in HIV/AIDS handling efforts. Gays were homosexuals who were closely related to HIV/AIDS. HIV prevalence of gays in Semarang city was 12%. Doctors and nurses were health workers who had an important role in HIV/AIDS handling efforts. The objective of this study was to see the role of doctors and nurses in HIV/AIDS handling efforts of the gays.This research applied a socio-legal approach and analytical descriptive specification. This research used primary and secondary data. The primary data were gathered through interviews and field observation. The informants were eight members of gay community while the other informants were the head of the community beside doctors and nurses of Halmahera Health Center. The secondary data were obtained through literature studies particularly having relation with the role of doctors and nurses in handling HIV/AIDS to the gays. The data were then qualitatively analyzed.The results of the study showed that the doctors and nurses had well accomplished their role in handling HIV/AIDS for the gays but it had not been accomplished in accordance with the provisions of the existing legislation. In handling HIV/AIDS to gays, a doctor had a role as a care provider, a decision maker and a communicator of the actions that should be given to the patients, while a nurse had a role as a care giver and a counsellor by providing diagnoses and appropriate nursing care to the patients as needed. The supporting factors were the availability of health facilities, health resources and adequate infrastructure whereas the inhibiting factors were lack of health personnel as a counselor and lack of self-disclosure of the gays